Quantification of the efficacy of collagen cross-linking agents to induce stiffening of rat sclera. Issue 129 (30th April 2017) - Campbell, Ian C.; Hannon, Bailey G.; Read, A. Thomas; Sherwood, Joseph M.; Schwaner, Stephen A.; Ethier, C. Ross
Abstract : The concept of scleral stiffening therapies has emerged as a novel theoretical approach for treating the ocular disorders glaucoma and myopia. Deformation of specific regions of the posterior eye is innately involved in the pathophysiology of these diseases, and thus targeted scleral stiffening could resist these changes and slow or prevent progression of these diseases. Here, we present the first systematic screen and direct comparison of the stiffening effect of small molecule collagen cross-linking agents in the posterior globe, namely using glyceraldehyde, genipin and methylglyoxal (also called pyruvaldehyde). To establish a dose–response relationship, we used inflation testing to simulate the effects of increasing intraocular pressure in freshly harvested rat eyes stiffened with multiple concentrations of each agent. We used digital image correlation to compute the mechanical strain in the tissue as a metric of stiffness, using a novel treatment paradigm for screening relative stiffening by incubating half of each eye in cross-linker and using the opposite half as an internal control. We identified the doses necessary to increase stiffness by approximately 100%, namely 30 mM for glyceraldehyde, 1 mM for genipin and 7 mM for methylglyoxal, and we also identified the range of stiffening it was possible to achieve with such agents. Such findings will inform development of in vivo studies of scleral stiffening to treat glaucoma and myopia.